2011
DOI: 10.1007/s10393-011-0725-7
|View full text |Cite
|
Sign up to set email alerts
|

Rodent-Borne Hantaviruses in Cambodia, Lao PDR, and Thailand

Abstract: In order to evaluate the circulation of hantaviruses present in southeast Asia, a large scale survey of small mammal species was carried out at seven main sites in the region (Cambodia, Lao People's Democratic Republic, and Thailand). Small scale opportunistic trapping was also performed at an eighth site (Cambodia). Using a standard IFA test, IgG antibodies reacting to Hantaan virus antigens were detected at six sites. Antibody prevalence at each site varied from 0 to 5.6% with antibodies detected in several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…This phylogenetic analysis was also performed with a reduction of the S CDS dataset to 519 nucleotides (positions 364-882). This allowed the inclusion of the sequences of Cambodian strains close to THAIV, and of other THAIV sequences (Reynes et al 2003, Hugot et al 2006, Blasdell et al 2011. Although the tree topology changed slightly and the statistical support was lower, all sequences grouped together (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This phylogenetic analysis was also performed with a reduction of the S CDS dataset to 519 nucleotides (positions 364-882). This allowed the inclusion of the sequences of Cambodian strains close to THAIV, and of other THAIV sequences (Reynes et al 2003, Hugot et al 2006, Blasdell et al 2011. Although the tree topology changed slightly and the statistical support was lower, all sequences grouped together (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis shows that at least nine clades of HTNV and five clades of SEOV are prevalent in China Zou et al, 2016), including the Xinyi and Fugong viruses that have been recently reported in specific epidemic foci (Ge et al, 2016;Gu et al, 2016). Rodent-borne hantaviruses have also been detected in Lao PDR, Thailand (Thailand hantavirus, THAIV) and Cambodia (THAIV-like virus) (Blasdell et al, 2011;Pattamadilok et al, 2006). Among those viruses, THAIV can cause disease in humans (Pattamadilok et al, 2006;Gamage et al, 2011).…”
Section: Pathogenic Hantaviruses and Their Reservoirsmentioning
confidence: 99%
“…Hantavirus-infected rodents have been reported in Southeast Asian countries including Vietnam, Cambodia, Thailand and Singapore [2,9,12,18,21]. Antibody positivity among humans has also been reported in Asian countries including India, Sri Lanka and Vietnam [3,5,7].…”
Section: Discussionmentioning
confidence: 99%